Occurrence of persistent atrial fibrillation during pacing for sinus node disease: The influence of His bundle pacing versus managed ventricular pacing. (18th November 2020) - Pastore, Gianni; Marcantoni, Lina; Lanza, Daniela; Maines, Massimiliano; Noventa, Franco; Corbucci, Giorgio; Rigatelli, Gianluca; Baracca, Enrico; Roncon, Loris; Zanon, Francesco
Abstract: Introduction: In patients with sinus node disease (SND), the dual‐chamber pacemaker (PM) is programmed in DDDR mode with an algorithm to avoid unnecessary right ventricular (RV) pacing. This pacing mode may prolong PR interval with consequently atrioventricular (AV) asynchrony which is associated with a higher risk of atrial fibrillation (AF). We evaluate whether preserving AV synchrony by setting a fixed AV delay during physiological RV pacing, that is,  His bundle pacing (HBP), could reduce the risk of AF occurrence in comparison with a standard pacing mode with an algorithm to avoid unnecessary RV pacing (DDD‐VPA). Methods and Results: We collected retrospective data from 313 consecutive patients who had undergone PM for SND. The first occurrence of persistent AF (>7 consecutive days) as a function of the pacing mode was evaluated. HBP and DDD‐VPA were implemented in 82 and 231 patients, respectively. Persistent AF occurred in 128 (40.9%) patients over a median follow‐up of 70 months (67–105). The DDD‐VPA pacing mode was significantly correlated with the occurrence of persistent AF only when the basal PR was long (>180 ms). The risk of persistent AF was significantly lower in patients on HBP than in those on DDD‐VPA, adjusted HR = .57 (95% CI,  .36– .89, p =.014). Other independent predictors of persistent AF occurrence were: A history of AF (HR = 3.91; 95% CI, 2.48–6.19, p  = .001), age, and long PR interval (HR = 2.98; 95% CI, 2.00–4.43, p =.001). Conclusion: In SND patients and long basal PR interval, the HBP may reduce the risk of persistent AF in comparison with the DDD‐VPA.